ANALISIS TIMBULAN, KOMPOSISI DAN KARAKTERISTIK SAMPAH DI KOTA PADANG - Nizwardi Azkha (Faculty of Public Health, Andalas University, 2006)
There are still some household throw away garbage in promiscuoulsy place and not yet all garbage managed better by Padang government. The goal of this research for arise, composition and characteristics analysis garbage domestic in Padang City. The result of research for arise of garbage from domestic its avarage 2,26 l/p/days. The composition of garbage domestic consist of organic garbage 94,24% and anorganic garbage 5,75 %. For Physics cover to specific gravity (0,15 kg/l), size measure 250 mm (54,86%). For chemical to cover dampness (32%), volatil rate (58%), dusty rate (10%), C/N ratio (27,30) and enery content 7422 Btu/lb. For biology of size measure wearedby crowded fly of garbage during six hour obtained density of fly 7/ grill fly. For the planning of management of ideal garbage in Padang city, dissociating garbage start from home doorstep, need the existence of socialization in making of compost, and also management with sanitary landfill system or incenerator also still represent good enough alternative.